2016
DOI: 10.1007/s00264-016-3188-1
|View full text |Cite
|
Sign up to set email alerts
|

Early clinical and radiological outcomes of reverse shoulder arthroplasty with an eccentric all-polyethylene glenosphere to treat failed hemiarthroplasty and the sequelae of proximal humeral fractures

Abstract: Level 4, retrospective therapeutic case series.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 36 publications
1
19
0
Order By: Relevance
“…However, patients coming from conservative treatment of the index proximal humeral fracture did significantly better in the Constant Score in terms of absolute forward elevation and external rotation when compared to patients coming from ORIF. The complication rate observed was similar to what has been reported (14,8%) 8, 11, 12, 13, 15, 16, 17, 18, 20, 21, 22, 23, 24. Although it did not reach significance, there was a trend towards a higher complication rate in the ORIF group when compared to the conservative group.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…However, patients coming from conservative treatment of the index proximal humeral fracture did significantly better in the Constant Score in terms of absolute forward elevation and external rotation when compared to patients coming from ORIF. The complication rate observed was similar to what has been reported (14,8%) 8, 11, 12, 13, 15, 16, 17, 18, 20, 21, 22, 23, 24. Although it did not reach significance, there was a trend towards a higher complication rate in the ORIF group when compared to the conservative group.…”
Section: Discussionsupporting
confidence: 88%
“…They include mal-unions, non-unions, cephalic avascular necrosis, a loss of reduction and hardware complications 1, 2, 3, 4. Surgery of fracture sequelae is challenging and usually leads to limited functional results and may also result in a high complication rate 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, whereas most series of PHFS in the literature have been heterogeneous and included RSA for failed hemiarthroplasty, our series is homogeneous. 17,20,28 We believe that our study adds substantially to the existing literature, providing useful information with clear clinical applications for shoulder surgeons.…”
Section: Discussionmentioning
confidence: 73%
“…Traditionally, RTSA was used primarily as a salvage procedure after failed HA, ORIF, or nonoperative fracture sequelae when no other options remained. [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24] However, these patients frequently experience only mild improvements in their activities of daily living (ADLs) 15,25 and face a high risk of complications. 24,26,27 Several systematic reviews have suggested that RTSA may be superior to HA for acute PHFs [28][29][30] and in recent years RTSA has become an increasingly popular initial option for these injuries.…”
Section: Introductionmentioning
confidence: 99%